Synthesis and Antiproliferative Activities of Conjugates of Paclitaxel and Camptothecin with a Cyclic Cell-Penetrating Peptide - El-Sayed, Naglaa Salem (Molecules, 2019)
Cell-penetrating peptide [WR](5) has been previously shown to be an efficient molecular transporter for various hydrophilic and hydrophobic molecules. The peptide was synthesized using Fmoc/tBu solid-phase chemistry, and one arginine was replaced with one lysine to enable the conjugation with the anticancer drugs. Paclitaxel (PTX) was functionalized with an esterification reaction at the C2′ hydroxyl group of PTX with glutaric anhydride and conjugated with the cyclic peptide [W(WR)(4)K(βAla)] in DMF to obtain the peptide-drug conjugate PTX1. Furthermore, camptothecin (CPT) was modified at the C(20)-hydroxyl group through the reaction with triphosgene. Then, it was conjugated with two functionalized cyclic peptides through a formyl linker affording two different conjugates, namely CPT1 and CPT2. All the conjugates showed better water solubility as compared to the parent drug. The cytotoxicity assay of the drugs and their conjugates with the peptides were evaluated in the human breast cancer MCF-7 cell line. PTX inhibited cell proliferation by 39% while the PTX-peptide conjugate inhibited the proliferation by ~18% after 72 h incubation. On the other hand, CPT, CPT1, and CPT2 reduced the cell proliferation by 68%, 39%, and 62%, respectively, in the MCF-7 cell lines at 5 µM concentration after 72 h incubation.